BOOK REVIEW: Tim Marshall, "Prisoners of Geography: Ten Maps That Tell You Everything You Need To Know About Global Politics", Elliott & Thompson, London, 2015; "The Power of Geography: Ten Maps that Reveal the Future of Our World", Elliott & Thompson, London, 2021 - ONACIU, Vlad (Studia Universitatis Babeș-Bolyai Historia, 2022)
The war in Ukraine and the rise of China’s influence are reshaping geopolitics. Our world is changing and we are trying to understand these phenomena with the aid of a variety of lenses. One approach puts an emphasis on the role of geography and its influence on policy and decision-making. Tim Marshall attempted to explain and teach about our world through his two well-known books: Prisoners of Geography: Ten Maps That Tell You Everything You Need To Know About Global Politics and The Power of Geography: Ten Maps that Reveal the Future of Our World. It is also an exercise in trying to remind readers some of the basics, namely, understanding history and international relations by looking at maps.